2015
DOI: 10.1186/s12889-015-2125-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an intervention to enhance guideline adherence of occupational physicians on return-to-work self-efficacy in workers sick-listed with common mental disorders

Abstract: BackgroundSince a higher level of self-efficacy in common mental disorders is associated with earlier return-to-work (RTW), it is important to know if work related self-efficacy can be increased by occupational health care. The primary aim of this study was to evaluate whether an intervention to enhance guideline adherence of occupational physicians lead to an increase in RTW self-efficacy in workers three months later. The secondary aim was to evaluate whether the intervention modified the association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 42 publications
2
29
0
5
Order By: Relevance
“…If people with MI/MHI make insufficient effort to find or keep employment as a result of self-stigma, this increases their risk of unemployment. Whereas cognition is increasingly gaining attention in work rehabilitation research, such as research on return-to-work perceptions and return-to-work self-efficacy [44][45][46], studies on the long-term effects of self-stigma, anticipated discrimination and especially on the "Why Try" effect on unemployment are scarce and warrant more attention [47]. Moreover, considering the high prevalence of the "Why Try" effect, more intervention studies on how to overcome self-stigma and improve work-related self-efficacy are urgently needed.…”
Section: Social Stigma Definedmentioning
confidence: 99%
See 1 more Smart Citation
“…If people with MI/MHI make insufficient effort to find or keep employment as a result of self-stigma, this increases their risk of unemployment. Whereas cognition is increasingly gaining attention in work rehabilitation research, such as research on return-to-work perceptions and return-to-work self-efficacy [44][45][46], studies on the long-term effects of self-stigma, anticipated discrimination and especially on the "Why Try" effect on unemployment are scarce and warrant more attention [47]. Moreover, considering the high prevalence of the "Why Try" effect, more intervention studies on how to overcome self-stigma and improve work-related self-efficacy are urgently needed.…”
Section: Social Stigma Definedmentioning
confidence: 99%
“…Mental disorders are even more prevalent in young people: in OECD countries, approximately one in four 15 to 24 year-olds have a mental disorder, which puts them at a higher risk of dropping out of school and having poorer chances of finding stable employment [1]. A recent epidemiological study investigating the influence of different chronic health problems on loss of employment in workers aged [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] showed that workers with selfreported psychological health problems had the highest risk of unemployment. Moreover, compared to workers with other chronic health conditions, they also had a higher risk of other adverse occupational outcomes, such as taking early retirement and exiting the work force via disability benefits and sick leave [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies carried out with workers with a diagnosed mental disorder found that a delay of more than 3 weeks in the medical consultation after going on sick leave was one of the main factors predicting a long sick leave of between 3 and 6 months (Brouwers et al, 2009). In addition, different studies have shown that when there is an initial consultation with the work physician (not a mental health specialist) in the first 2 (Caballero-Martínez et al, 2014;Van Beurden et al, 2015) to 6 weeks (Nieuwenhuijsen, Verbeek, de Boer, Blonk, & van Dijk, 2005) of the sick leave, there is a reduction in the number of workers on long-term sick leave for common mental disorders. Other studies have found that the return to work occurs sooner when there has been follow-up by the work physician (previously trained by a psychiatrist), compared to care as usual Therefore, the studies mentioned above suggest that the time until initiating the evaluation and treatment by a healthcare professional of a patient on sick leave for a common mental health disorder is an important factor in the duration of the sick leave.…”
mentioning
confidence: 99%
“…Common mental health problems are mild-to-moderate depressive, anxiety, and stress-related complaints, which have also been described as common mental disorders (CMD) (1). The large impact of CMD on society has led to a growing attention in recent literature for the development and evaluation of interventions that aim to promote returnto-work (RTW) of workers on sick leave due to a CMD (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Many of these studies focused on sick-listed employees, ie, workers with an employment contract.…”
mentioning
confidence: 99%